The language of civil proceedings and interpretation as procedural guarantees for foreign persons - Muidenova А.К.; Issayeva А.Ж.; Zhumadilova М.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
The article examines pressing issues related to safeguarding the linguistic rights of foreign persons in civil proceedings of the Republic of Kazakhstan. The purpose of the study is to conceptualize the language of judicial proceedings and the institution of interpretation as fundamental structural guarantees of the right to judicial protection in the context of the internationalization of private-law disputes. The object of the research comprises civil procedural relations involving foreign persons, while the subject encompasses the legal mechanisms for the implementation of the principle of the language of proceedings and the provision of high-quality interpretation. The study has yielded the following significant findings: it is substantiated that the language of judicial proceedings constitutes an autonomous element of procedural form, ensuring legal certainty and equality of the parties. It is revealed that the existing regional asymmetry in the use of the state and official languages in Kazakhstan, along with regulatory lacunae in Article 14 of the Civil Procedure Code of the Republic of Kazakhstan concerning criteria for the quality of interpretation, generates risks of a formalistic approach to the realization of the rights of foreign nationals. The authors argue that inadequate interpretation should be classified as a substantial procedural violation distorting the adversarial balance and the principle of “equality of arms.” The theoretical significance lies in shifting from the perception of interpretation as a technical service to its understanding as a legally significant procedural act directly affecting the lawfulness of judicial decisions. The practical value of the study consists of proposing measures aimed at the professionalization of court interpretation, including the establishment of national registers of certified specialists and the development of standards for assessing the quality of linguistic assistance in the context of the digitalization of justice.